Political Reform: A Muhammad Ghazali’s Perspective (Salam International Academic Journal, 2014)
In this study, Sheikh Muhamad Al-Gazali’s views on politics and government are collected. The views that underpins political reforms in the contemporary period. His opinions are mainly in four areas:First: His views about Government: Sheikh believes that Government and Ruling is an obligation of ruler who is responsible towards Allah and the people. Being a ruler and president is not a position to be proud of, rather it’s a position to serve the people that he took agreed with. Ruler from Islamic perspective is a most competent person who is elected by the people for leadership. In the whole Islamic History, the inheritance of the leadership has been the most disturbing issue and reason for the backwardness and caused Muslims to lag behind the caravan of civilization and inventions.The second aspect is about the Shura (Council): Sheikh believes that the political system of Islam is based on Shura (Coucil) and people are the source of power. For him, Shura works on the matters and areas only where there is possibility of Ijtihaad (Judgement) and there religious text available. While in the existence of religious text no election or vote is considered valid. He says that in general affairs, the Shura with its binding nature is a restraint for tyranny, while it prevents the monopoly of decision making by one person. For Ghazali, the recommendations of the council is better than opinion of one person, hence he rejects the authority of ruler to ignore council’s opinion. For him, the power that is not based on the opinion of the people is illegitimate. He condemns the views of some scholars who back the rulers to use oppression and injustice. Al-Ghazali opines that the decision making must be prudent and be based on scientific researches which carries greater good.The 3rd aspect of Al-Ghazali’s is about the Tyranny. He believes that tyranny is greater evil and control of entire nation by one person is not only against religious teachings but also it is against sound wisdom.Al-Ghazali sees tyranny as the reason for the backwardness of the Muslim nation while he considers it a coup against religious commands. For Him, Islam liberates humanity to be enslaved by other human, while the tyranny revives the tradition of enslavement.The fourth aspect of his political reform is about Imperialism. He views imperialism as way of exploitation of a nation by the other directly or if not possible, indirectly through the clients and oppressive rulers. Hence, it is imperative to address this issue in the Muslim world.
Keywords: Political Reform; Islamic World; Ruler; Tyranny; Shura (Consultation)